СТРУКТУРА И ТЕНДЕНЦИИ МЕЖДУНАРОДНОЙ РЕГИОНАЛЬНОЙ ЭКОНОМИЧЕСКОЙ ИНТЕГРАЦИИ - Сун, Ли (Journal of Economic Research & Business Administration, 2015)
The article analyzed the present situation of international regional economic cooperation and sub-regional economic cooperation, worked out the perspective of their development.